2006
DOI: 10.1134/s000629790602009x
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition and native state of pigments of thylakoid membrane of wheat genotypes differently tolerant to water stress

Abstract: Protein composition and native state of chlorophylls were analyzed in two wheat (Triticum durum L.) genotypes with different tolerance to drought, Barakatli-95 (drought-tolerant) and Garagylchyg-2 (drought-sensitive), during water deficit. It is shown that the plants subjected to water deficit appear to have a slight increase in alpha- and beta-subunits of CF1 ATP-synthase complex (57.5 and 55 kD, respectively) in Barakatli-95 and their lower content in Garagylchyg-2. Steady-state levels of the core antenna of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Similarly, higher level of carotenoids and lower membrane damage characterizes the drought-exposed tolerant wheat genotype relative to the sensitive one (Chandrasekar et al 2000, Sairam andSaxena 2000). Recent data describing the modified absorption spectra of carotenoids in drought-sensitive wheat genotypes in contrast to the conserved spectra of tolerant ones (Guseynova et al 2006) give support to our result.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, higher level of carotenoids and lower membrane damage characterizes the drought-exposed tolerant wheat genotype relative to the sensitive one (Chandrasekar et al 2000, Sairam andSaxena 2000). Recent data describing the modified absorption spectra of carotenoids in drought-sensitive wheat genotypes in contrast to the conserved spectra of tolerant ones (Guseynova et al 2006) give support to our result.…”
Section: Discussionsupporting
confidence: 86%
“…2000, Sairam and Saxena 2000). Recent data describing the modified absorption spectra of carotenoids in drought‐sensitive wheat genotypes in contrast to the conserved spectra of tolerant ones (Guseynova et al. 2006) give support to our result.…”
Section: Discussionsupporting
confidence: 86%
“…In a drought-resistant genotype of wheat (Triticum aestivum), the induction of a protein homologous to BnD22 identified in the thylakoid membrane showed a significant role for BnD22 during the stress response (Guseynova et al, 2006). In our study, BnD22 represented up to 9% of the leaf soluble protein content in plants treated with MeJA, whereas it represented approximately 1% of the soluble protein content in plants adapted to drought (Downing et al, 1992;Ilami et al, 1997).…”
Section: Discussionmentioning
confidence: 76%
“…The decrease in the content of D1 and D2 proteins in the thylakoid membranes from water‐stressed plants (especially in the modern cultivars Lc8275 and Gc20) seems to be due, in part, to their enhanced stress tolerance (Guseynova et al. ). High rates of D1‐protein turnover provide stability to thylakoid membranes and their electron transport chain from the damaging action of free radicals formed under stress conditions (Fan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lu and Zhang (1999) and Shangguan et al (2000) also suggested that under mild water stress, PS2 photochemistry was not affected and was resistant to water deficits, supporting the observation that gs was important in reducing P N . The decrease in the content of D1 and D2 proteins in the thylakoid membranes from water-stressed plants (especially in the modern cultivars Lc8275 and Gc20) seems to be due, in part, to their enhanced stress tolerance (Guseynova et al 2006). High rates of D1-protein turnover provide stability to thylakoid membranes and their electron transport chain from the damaging action of free radicals formed under stress conditions (Fan et al 2009).…”
Section: Ps2 Photochemistry Of Spring Wheat Cultivars Under Drought Smentioning
confidence: 99%